Differences in patient perceptions of integrated care among black, hispanic, and white Medicare beneficiaries. (11th February 2021) - Ling, Emilia J.; Frean, Molly; So, Jody; Tietschert, Maike; Song, Nancy; Covington, Christian; Bahadurazada, Hassina; Khurana, Sonia; Garcia, Luis; Singer, Sara J.
Abstract: Objective: This study sought to identify potential disparities among racial/ethnic groups in patient perceptions of integrated care (PPIC) and to explore how methodological differences may influence measured disparities. Data Source: Data from Medicare beneficiaries who completed the 2015 Medicare Current Beneficiary Survey (MCBS) and were enrolled in Part A benefits for an entire year. Study Design: We used 4‐point measures of eight dimensions of PPIC and assessed differences in dimensions among racial/ethnic groups. To estimate differences, we applied a "rank and replace" method using multiple regression models in three steps, balancing differences in health status among racial groups and adjusting for differences in socioeconomic status. We reran all analyses with additional SES controls and using standard multiple variable regression. Data Collection/Extraction Methods: Not applicable. Principal Findings: We found several significant differences in perceived integrated care between Black versus White (three of eight measures) and Hispanic versus White (one of eight) Medicare beneficiaries. On average, Black beneficiaries perceived more integrated support for self‐care than did White beneficiaries (mean difference = 0.14, SE = 0.06, P =.02). Black beneficiaries perceived more integrated specialists' knowledge of past medical history than did White beneficiaries (mean difference = 0.12, SE = 0.06, P =.01). Black and Hispanic beneficiaries also each reported, on average, 0.18 more integrated medication and home health management than did White beneficiaries ( P <.01 and P <.01). These findings were robust to sensitivity analyses and model specifications. Conclusions: There exist some aspects of care for which Black and Hispanic beneficiaries may perceive greater integrated care than non‐Hispanic White beneficiaries. Further studies should test theories explaining why racial/ethnic groups perceive differences in integrated care.